Tourism : principles, practices, philosophies / Charles R Goeldner, J R Brent Ritchie - Goeldner, Charles R
Updated and expanded for the twenty-first century, this classic text remains the #1 introduction to tourism principles and practices. Now in its ninth edition, Tourism provides a comprehensive introduction to the world's most rapidly growing industry. Tens of thousands of hospitality and tourism students worldwide have used previous editions of this classic text to launch their professional careers. Written by two internationally recognized experts, this book looks at the travel and tourism industry from a global perspective, offering insights into the economic, political, and social forces th.